Penerapan Metode EUCS Untuk Evaluasi Tingkat Kepuasan Pengguna Aplikasi PNM Digi Karyawan - Ima Irumas; Joy Nashar Utamajaya (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
The PNM Digi Employee application was designed by PT. PNM Mekaar Persero to make it easier for employees to perform attendance and some administrative services for daily needs such as bill payments, purchase of credit, investments and many more. The purpose of this study was to determine the level of employee satisfaction in using the PNM Digi Employee application. User satisfaction was measured so that it became input for the company in managing and developing the PNM Digi Employee application. For this reason, this study was conducted to measure the level of user satisfaction of the Digi Employee PNM application by applying the End User Computing Satisfaction method. To obtain data as research material, research questionnaires were distributed to employees by adopting the dimensions of the End User Computing Satisfaction method, namely the dimensions of Content, Accuracy, Format, Easy of Use and Timeliness. It was found that the employees of PT. PNM Mekaar is very satisfied in using the PNM Digi Employee application based on the results of the tests that have been carried out showing the percentage of all dimensions is worth above 80%, namely the Content dimension 85.3%, Accuracy dimension 83.7%, Format dimension 86.6%, Easy of dimension. Use 85.3% and Timeliness dimensions 86% with dimensions that have a significant effect, namely the dimensions of format and dimensions of Timeliness.